Peran Informasi Akuntansi Manajemen Mengenai Pengambilan Keputusan Investasi Aktiva Tetap Pada Koperasi Jasa Angkutan di Jawa Timur - Eny Rochmatulaili; Jaka Dwi Saputra (Fakultas Ekonomi Universitas Yos Soedarso, 2020)
Koperasi Jasa Angkut is a cooperative that houses East Java Tourism transportation. One of the excellent facilities owned by East Java Tourism is the presence of vehicles that can take tourists from the bus park (terminal) to the East Java Tourism location. Here the Cooperative management requires management accounting information in analyzing the procurement of fixed assets in the place / terminal of Tourism which finally after that, the Cooperative can determine a decision.The purpose of this study was to determine the role of management accounting information in the decision making of Cooperative fixed assets investment. This research is a qualitative case study. Data collection methods include documentation, interviews and observations.The results of research conducted at the Transportation Services Cooperative in East Java show that cooperative management has used differential accounting information in making decisions on fixed asset investment, namely by buying elves in Malik Ibrahim Gresik Terminal based on smaller costs. Cooperatives should be more careful in assessing the relevant costs for making long-term investment decisions and evaluation should also be carried out so that further planning can obtain satisfactory results.Â Keywords: Management accounting information ; Fixed asset investment